2019
DOI: 10.1111/sapm.12277
|View full text |Cite
|
Sign up to set email alerts
|

Riemann‐Hilbert problem and matrix discrete Painlevé II systems

Abstract: Matrix Szegő biorthogonal polynomials for quasi‐definite matrices of Hölder continuous weights are studied. A Riemann‐Hilbert problem is uniquely solved in terms of the matrix Szegő polynomials and its Cauchy transforms. The Riemann‐Hilbert problem is given as an appropriate framework for the discussion of the Szegő matrix and the associated Szegő recursion relations for the matrix orthogonal polynomials and its Cauchy transforms. Pearson‐type differential systems characterizing the matrix of weights are studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…De nition 3. Motivated by (19) and (21) we introduce two linear operators L and R , acting on the linear space of polynomials C N×N [z] as follows L (P) := zP + P a L (z) + Pb L (z), R (P) := zP + a R (z)P + b R (z)P.…”
Section: Adjoint Operatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…De nition 3. Motivated by (19) and (21) we introduce two linear operators L and R , acting on the linear space of polynomials C N×N [z] as follows L (P) := zP + P a L (z) + Pb L (z), R (P) := zP + a R (z)P + b R (z)P.…”
Section: Adjoint Operatorsmentioning
confidence: 99%
“…in the whole space of parameters except possibly for algebraic subvarieties. The situation was considered in [19] for the matrix extension of the Szegő polynomials in the unit circle and corresponding non-Abelian versions discrete Painlevé II equations.…”
mentioning
confidence: 99%
“…It was found that the singularity confinement holds generically, i.e., in the whole space of parameters except possibly for algebraic subvarieties. This situation was considered in [51] for the matrix extension of the Szegő polynomials in the unit circle and corresponding non-Abelian versions of discrete Painlevé II equations.…”
Section: Introductionmentioning
confidence: 99%
“…This Riemann–Hilbert formulation is a powerful methodology to obtain algebraic and differential identities for MVOPs, as well as for the functions of the second kind, and it has been extensively used in the last few years, we refer the reader to Refs. 25–27 and to Refs. 28, 29 for matrix orthogonal polynomials of Hermite and Laguerre type on the real line or the positive half‐line.…”
Section: Introductionmentioning
confidence: 99%